EKONOMI KREATIF DAN INDUSTRI HALAL SEBAGAI MOTOR PERTUMBUHAN EKONOMI PASCA-PANDEMI DI INDONESIA - Fikri Novrial Azhar (LPPM INSTITUT AGAMA ISLAM HASANUDDIN PARE, 2025)
The Covid-19 pandemic has had a significant impact on the Indonesian economy, but at the same time it has opened up opportunities for certain sectors to become the engine of economic recovery. The creative economy and the halal industry are considered to have a strategic role because both are based on creativity, innovation, and cultural and sharia values. This study uses a qualitative approach with a literature review method, focusing on analyzing the potential, challenges, and synergies between the creative economy and the halal industry in driving post-pandemic economic growth. The results of the study show that the creative economy is capable of creating added value through innovation, design, and the use of digital technology, while the halal industry provides quality assurance and certainty of product halalness. The synergy between the two strengthens the competitiveness of local products, expands domestic and global markets, and accelerates economic recovery. However, a number of challenges remain, including low halal literacy, limited access to financing, complex certification bureaucracy, and low digital literacy among MSMEs. Therefore, multi-stakeholder collaboration, strengthening of a research and technology-based innovation ecosystem, and regulatory and financing support are needed for Indonesia to solidify its position as a global halal economic center. Keywords : Creative Economy, Halal Industry, Economic Growth, Post-Pandemic